ХОРАЗМ ХАЛФАЧИЛИК АНЪАНАЛАРИНИНГ ТАДҚИҚ ЭТИЛИШИ - Сабирова, Н.Э. (SCIENCE and SOCIETY, 2022)
This article mentions the study of Khorezmian calligraphy within the republic. There is shawn aspects of their creativity and performance, in harmony with the literature. The issues of teaching musicology are also discussed. The directions of this ancient art are highlighted the place of halfa in the art of epic and singing. The article provides extensive information on the study of the art of the Khorezm Caliphate.